Optimization of In Vitro Microcloning of Lagochilus inebrians Bunge - Sultonova, Kumush; Alikulov, Begali; Xasanov, Normat; Abdullayeva, Yulduz; Sharopova, Shahnoza; Jabborov, Baxtiyor; Hotamova, Hulkar; Dilshoda, Mamadiyarova; Khusniddin, Boymurodov (Pandawa Institute, 2025)
In the following years, introduction (in situ) of rare and promising medicinal plants, determination of morphological and ecological adaptability to selected soil and climate conditions, and obtaining pathogen-free seedlings through microclonal (in vitro) reproduction in areas affected by environmental stress factors creation of plantations are gaining importance. This research aimed at choosing the optimal conditions for obtaining pathogen-free seedlings of Lagochilus inebrians in vitro and acclimatization in arid conditions. The optimal amounts of added phytohormones were chosen to increase the efficiency of the nutrient media used in the microconal propagation of L. inebrians, based on the possibility of acclimatization in arid conditions. The obtained results serve to multiply L. inebrians in vitro and create plantations in arid regions based on the obtained seedlings.